Detection of antibiotic resistance genes β-lactamics in bacterial strains isolated from Umbilical Cord Blood Units for transplant - J.M. Bello-López; J. Rojo-Medina (Revista Médica del Hospital General de México, 2017)
Introduction: Among the risks associated with hematopoietic stem cells transplantation of umbilical cord blood are bacterial infections. This becomes dangerous when bacterial sepsis is related to resistance to antibiotics commonly used to eliminate of this type infections. Among the widely used antibiotics are those of the β-lactam family. Among the genes responsible for the resistance are designated “bla genes” which encode for broad-spectrum lactamases. Its detection in the laboratory shown the importance in the manufacture of cord blood units. Objective: To correlate the antibiotic resistance in bacterial contaminants isolated from Umbilical Cord Blood Units (UCBU), with detection of genes encoding resistance of β-lactamics antibiotics. Materials and methods: Test of resistance to antibiotics was determined in 107 bacterial strains using disk diffusion method according to the recommendations of “The Clinical and Laboratory Standards Institute (CLSI)” and multiplex amplification by PCR of genes blaTEM, blaSHV and blaCTX-M were performed in order to detect genetic elements associated to antimicrobial resistance tested. Results: Broad-spectrum penicillins showed lower inhibitory activity on the tested strains. Gene detection by multiplex PCR of encoding antimicrobial resistance (β-lactamases) revealed the presence of bla–HSV, blaCTX-M and bla–TEM genes in most strains tested even when these genes have been reported in Enterobacteriaceae family members. Conclusions: The genotype detection encoding antibiotic resistance in isolates of UCBU clearly indicates the potential risk of sepsis difficult to eradicate in the patient, if present in a UCBU available for transplant. Additionally, the existence of these genes reveals horizontal transfer events of genetic material between bacteria. So the importance to realize this studies before transplant.